PopB-PcrV Interactions Are Essential for Pore Formation in the Pseudomonas aeruginosa Type III Secretion System Translocon - Emma Kundracik; Josephine Trichka; José Díaz Aponte; Alicia Roistacher; Arne Rietsch (mBio, 2022)
ABSTRACT The type III secretion system (T3SS) is a syringe-like virulence factor that delivers bacterial proteins directly into the cytoplasm of host cells. An essential component of the system is the translocon, which creates a pore in the host cell membrane through which proteins are injected. In Pseudomonas aeruginosa, the translocation pore is formed by proteins PopB and PopD and attaches to the T3SS needle via the needle tip protein PcrV. The structure and stoichiometry of the multimeric pore are unknown. We took a genetic approach to map contact points within the system by taking advantage of the fact that the translocator proteins of P. aeruginosa and the related Aeromonas hydrophila T3SS are incompatible and cannot be freely exchanged. We created chimeric versions of P. aeruginosa PopB and A. hydrophila AopB to intentionally disrupt and restore protein-protein interactions. We identified a chimeric B-translocator that specifically disrupts an interaction with the needle tip protein. This disruption did not affect membrane insertion of the B-translocator but did prevent formation of the translocation pore, arguing that the needle tip protein drives the formation of the translocation pore. IMPORTANCE Type III secretion systems are integral to the pathogenesis of many Gram-negative bacterial pathogens. A hallmark of these secretion systems is that they deliver effector proteins vectorially into the targeted host cell via a translocation pore. The translocon is crucial for T3SS function, but it has proven difficult to study biochemically and structurally. Here, we used a genetic approach to identify protein-protein contacts among translocator proteins that are important for function. This genetic approach allowed us to specifically break a contact between the translocator PopB and the T3SS needle tip protein PcrV. Breaking this contact allowed us to determine, for the first time, that the needle tip actively participates in the assembly of the translocation pore by the membrane-bound pore-forming translocator proteins. Our study therefore both expands our knowledge of the network of functionally important interactions among translocator proteins and illuminates a new step in the assembly of this critical host cell interface.